Na tropie literatury bułgarskiej w Polsce w 2015 roku - Gołek-Sepetliewa, Dorota (Przekłady Literatur Słowiańskich, 2016)
On the trail of Bulgarian literature in Poland in 2015 The article comments on the presence of Bulgarian literature in Poland in 2015 from the perspective of genre forms, conventions, stylistic devices, and topics. In the abovementioned year, translations (by Hanna Karpinska) of the following works were published: Kalin Terziyski’s collection of short stories Is there anybody to love you?, Zachary Karabashliev’s road novel 18% gray, and Georgi Tenev’s crime drama The Evil Prince. The writers created texts that elicit strong emotions, based on realistic convention, in a simplified, accessible style. Terziyski and Karabashliev created a reality recognized by the reader, in which at the forefront there is the present social and cultural situation along with the problems of modern man (the breakdown of interpersonal relationships, as well as feelings of dissatisfaction, loneliness, and misery, accompanied by the desire for true love, devotion, and dedication). Tenev presents a crime drama based on the current elements of the political and social life, thereby exposing corrupt and criminal practices. Key words: Kalin Terziyski, Georgi Tenev, Zachary Karabashliev, Bulgarian literature in Poland